Two Ways. Pawel Jasienica on the Era of the January Uprising - Sikorska-Kowalska, Marta (Sensus Historiae, 2019)
Dwie drogi (Two Ways) is a book where Paweł Jasienica strongly emphasizes the importance of The January Uprising. He decidedly approved and agreed with the decision on starting uprising. His book covers three key historical problems: enfranchisement of peasants, the role of “the Reds” and “the Whites” in the uprising, and the characterisation of outstanding individuals. According to Jasienica, the governor of Warsaw Stefan Bobrowski was the most important commander. The main thesis of the book claims: “January Uprising stabilised the foundations of modern Poland, . . . the year 1863 started preparing the 1918 rebirth. The thesis which can and should be repeated.”